Investigation of Occupational Asthma: Do Clinicians Fail to Identify rRelevant Occupational Exposures? - Carlo de Olim; Denis Bégin; Louis-Philippe Boulet; André Cartier; Michel Gérin; Catherine Lemière (Canadian Respiratory Journal)
BACKGROUND: Specific inhalation challenges (SIC) enable the identification of the agent responsible of occupational asthma (OA). A clinician may fail to identify a specific agent in the workplace, which may potentially lead to a misdiagnosis. The expert assessment method performed by an occupational hygienist has been used to evaluate occupational exposures in epidemiological studies.